Promoting Good Governance, Development and Accountability - Brown-Shafii, S. author. aut Link
XV, 251 p.
Keywords: In addressing the politics of the international regulation of public procurement, this book fills a major gap in the literature. Brown-Shafii does this by investigating whether a WTO Agreement can be used to promote good governance, development and accountability.